IL-17 signaling protects against Helicobacter pylori-induced gastric cancer - Lee C. Brackman; Matthew S. Jung; Emily H. Green; Nikhita Joshi; Frank L. Revetta; Mark S. McClain; Nicholas O. Markham; M. Blanca Piazuelo; Holly M. Algood (Gut Microbes)
Helicobacter pylori infection is the predominant risk factor for the development of gastric cancer. Risk is enhanced by specific H. pylori virulence factors, diet, and the inflammatory response. Chronic activation of T helper (Th) 1 and Th17 pathways contributes to prolonged inflammation; yet, higher expression of IL-17 receptor (IL-17RA) is a favorable prognostic marker for survival after gastric cancer diagnosis. The protective impact of IL-17RA signaling is not understood. To investigate if IL-17RA signaling protects during H. pylori-induced carcinogenesis, the transgenic InsGAStg/tg mouse, which is prone to H. pylori-induced gastric cancer, was utilized. InsGAStg/tg mice and InsGAStg/tgIl17ra-/- mice were infected with a cag type 4 secretion system (T4SS) positive H. pylori strain for up to 6 months. Six weeks post-infection, IL-17RA deficiency led to increased bacterial burden, increased gastritis, and development of lymphoid follicles. Increased inflammation was associated with heightened cellular proliferation and earlier loss of parietal and chief cells in InsGAStg/tgIl17ra-/- mice. Gastric cancers developed more frequently by 3- and 6-months post-infection in H. pylori-infected InsGAStg/tgIl17ra-/- mice compared to InsGAStg/tg mice. Chronic inflammation was exacerbated with IL-17RA deficiency, characterized by elevated Th1/Th17 cytokines, increased B cell infiltration, and enhanced IgA production, despite reduced expression of the polymeric immunoglobulin receptor. Further, paragastric lymph nodes of InsGAStg/tgIl17ra-/- mice were enlarged relative to controls and displayed altered gene expression profiles. Increased inflammation was accompanied by a significant increase in Cybb expression, which encodes NADPH oxidase 2, suggesting that increased oxidative damage may occur in the absence of IL-17RA. Further, there is increased phosphorylation of histone 2AX in IL-17RA deficient mice, indicating that the DNA damage response is highly activated. These data suggest that IL-17RA signaling activates a protective pathway to prevent excessive inflammation which otherwise can lead to increased oxidative stress, DNA damage, and drive gastric carcinogenesis after H. pylori infection.